Characterization of ion-induced radiation effects in nuclear materials using synchrotron x-ray techniques. Issue 9 (20th May 2015) - Lang, Maik; Tracy, Cameron L.; Palomares, Raul I.; Zhang, Fuxiang; Severin, Daniel; Bender, Markus; Trautmann, Christina; Park, Changyong; Prakapenka, Vitali B.; Skuratov, Vladimir A.; Ewing, Rodney C.
Abstract: Abstract : Recent efforts to characterize the nanoscale structural and chemical modifications induced by energetic ion irradiation in nuclear materials have greatly benefited from the application of synchrotron-based x-ray diffraction (XRD) and x-ray absorption spectroscopy (XAS) techniques. Key to the study of actinide-bearing materials has been the use of small sample volumes, which are particularly advantageous, as the small quantities minimize the level of radiation exposure at the ion-beam and synchrotron user facility. This approach utilizes energetic heavy ions (energy range: 100 MeV–3 GeV) that pass completely through the sample thickness and deposit an almost constant energy per unit length along their trajectory. High energy x-rays (25–65 keV) from intense synchrotron light sources are then used in transmission geometry to analyze ion-induced structural and chemical modifications throughout the ion tracks. We describe in detail the experimental approach for utilizing synchrotron radiation (SR) to study the radiation response of a range of nuclear materials (e.g., ThO2 and Gd2 Ti x Zr2− x O7 ). Also addressed is the use of high-pressure techniques, such as the heatable diamond anvil cell, as a new means to expose irradiated materials to well-controlled high-temperature (up to 1000 °C) and/or high-pressure (up to 50 GPa) conditions. This is particularly useful for characterizing the annealing kinetics of irradiation-induced material modifications.